El reinado social de Jesucristo y el renacimiento católico argentino - Di Stefano, Roberto (Revista Brasileira de História das Religiões, 2025)
During the pontificates of Pius XI and Pius XII, Argentine Catholicism experienced its golden age: the number of dioceses and parishes multiplied, priestly ordinations increased, masse-scale lay organizations were created - notably Catholic Action, in 1931 - and the publication of books and magazines proliferated. This article aims to draw attention to aspects of this "Catholic revival" that, curiously, have not yet attracted the attention of historians: the theological, biblical pastoral, devotional, and liturgical foundations of this historical phenomenon that was, ultimately, and above all, a religious phenomenon.